2020
DOI: 10.1002/1878-0261.12738
|View full text |Cite
|
Sign up to set email alerts
|

Blood‐derived DNA methylation predictors of mortality discriminate tumor and healthy tissue in multiple organs

Abstract: Evidence has shown that certain methylation markers derived from blood can mirror corresponding methylation signatures in internal tissues. In the current study, we aimed to investigate two strong epigenetic predictors for life span, derived from blood DNA methylation data, in tissue samples of solid cancer patients. Using data from the Cancer Genome Atlas (TCGA) and the German DACHS study, we compared a mortality risk score (MRscore) and DNAmPhenoAge in paired tumor and adjacent normal tissue samples of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Further, it remains an open question in the field as to whether our blood-derived methylation results can be transferred to other cell types relevant to cancer development. A recent paper by Zhang et al suggests that blood-derived DNA methylation markers could mirror changes in difficult-to-access tissues relevant to cancer development [59]. While we were not able to study this particular question given our study methods, our results provide support for investigating these questions more directly in future studies.…”
Section: Discussionmentioning
confidence: 47%
“…Further, it remains an open question in the field as to whether our blood-derived methylation results can be transferred to other cell types relevant to cancer development. A recent paper by Zhang et al suggests that blood-derived DNA methylation markers could mirror changes in difficult-to-access tissues relevant to cancer development [59]. While we were not able to study this particular question given our study methods, our results provide support for investigating these questions more directly in future studies.…”
Section: Discussionmentioning
confidence: 47%
“…Because genome-wide DNA methylation studies show shared epigenomic features between aging and cancer, providing explanations for their possible molecular links [ 12 , 13 , 14 ], the role for DNAm age in carcinogenesis has been recently explored. The obtained results indeed indicate that DNAmaa increases cancer risk, promote cancer initiation or progression, and predict poor patient outcomes in different types of cancer [ 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, in some other cancers, DNAmad is associated with aggressive diseases and shorter survival.…”
Section: Introductionmentioning
confidence: 67%
“…Indeed, recent genome-wide analyses of DNA methylation have shown particular features shared between aging and cancer [ 1 , 4 , 13 , 14 ]. Importantly, the accelerated DNAm age in normal cells derived from healthy individuals is associated with increased cancer risk and cancer-related mortality [ 8 , 9 , 11 , 17 , 18 , 21 , 28 , 29 , 30 , 31 ]. Devall et al observed that higher DNAm age rates contributed to young age onset of colon cancer in African Americans [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is noteworthy to highlight that current research shows evidence that some DNA methylation markers derived from blood can mimic DNA methylation signatures found in internal tissues from primary cancer sources [ 34 ]. Therefore, this research can potentially help identify early-stage cancer by testing blood-derived samples using the proposed classification model.…”
Section: Resultsmentioning
confidence: 99%